High-Variability Phonetic Training enhances second language lexical processing: evidence from online training of French learners of English. Issue 3 (26th May 2021) - Melnik, Gerda Ana; Peperkamp, Sharon
Abstract: High-Variability Phonetic Training (HVPT) has been shown to be effective in improving the perception of the hardest non-native sounds. However, it remains unclear whether such training can enhance phonological processing at the lexical level. The present study tested whether HVPT also improves word recognition. Late French learners of English completed eight online sessions of HVPT on the perception of English word-initial /h/. This sound does not exist in French and has been shown to cause difficulty both at the prelexical (Mah, Goad & Steinhauer, 2016 ) and the lexical level of processing (Melnik & Peperkamp, 2019 ). In pretest and posttest participants were administered a prelexical identification task and a lexical decision task. Results demonstrate that after training the learners' accuracy improved in both tasks. Moreover, these improvements were retained four months after posttest. This is the first evidence that short training can enhance not only prelexical perception, but also word recognition.